Designing a sustainability monitoring system for the food and beverage industry in Indonesia using multidimensional scaling (MDS) - Barus, Wan Habibi Rahman; Sriwana, Iphov Kumala; Prambudia, Yudha (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
The decline in the performance of the food and beverage sector by -3% for the food sector and -26.39% for the beverage sector in the second quarter of 2020 due to the outbreak of Covid-19 necessitated an analysis of the sustainability of the food and beverage industry. This research aimed to analyze the sustainability of the industry. A monitoring system for the sustainability of the food and beverage industry was an essential tool to ensure that the sector operated sustainably and contributed positively to the environment and society. Multidimensional Scaling (MDS) could be used to analyze and visualize the sustainability performance of the food and beverage industry based on various relevant dimensions or factors. The simulation results of Rapid Assessment of Food and Beverages (RAP-FB) indicated an overall high level of sustainability at 64.89%. In summary, the research showed that the food and beverage (F&B) industry's sustainability could be assessed through various dimensions and factors (such as Gross Domestic Product (GDP), energy efficiency, and workplace safety) contributed significantly to its overall sustainability. The monitoring system based on MDS could provide valuable insights to enhance the industry's performance and ensure its continued positive impact on the environment and society.